Additive Manufacturing of Binary and Ternary Oxide Systems Using Two-Photon Polymerization and Low-Temperature Sintering - Halima El Aadad; Hicham El Hamzaoui; Yves Quiquempois; Marc Douay (Nanomaterials)
Multicomponent oxide systems have many applications in different fields such as optics and medicine. In this work, we developed new hybrid photoresists based on a combination of an organic acrylate resin and an inorganic sol, suitable for 3D printing via two-photon polymerization (2PP). The inorganic sol contained precursors of a binary SiO2-CaO or a ternary SiO2-CaO-P2O5 system. Complex microstructures were 3D printed using these hybrid photoresists and 2PP. The obtained materials were characterized using thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM) techniques. Our results revealed that the produced microstructures were able to endure sintering at 700 °C without collapsing, leading to scaffolds with 235 and 355 nm resolution and pore size, respectively. According to the TGA analysis, there was no significant mass loss beyond 600 °C. After sintering at 500 °C, the FTIR spectra showed the disappearance of the characteristic bands associated with the organic phase, and the presence of bands characteristic of the binary and ternary oxide systems and carbonate groups. The SEM images showed different morphologies of agglomerated nanoparticles with mean sizes of about 20 and 60 nm for ternary and binary systems, respectively. Our findings open the way towards precise control of bioglass scaffold fabrication with tremendous design flexibility.